ANALISA DAN PERANCANGAN SISTEM INFORMASI STIKES PRIMA JAMBI BERBASIS WEB - Lisdarti - (JURNAL AKADEMIKA)
The development of Green Technology Has Eye Opening ' global society and make wordpress page becoming increasingly narrow because hearts time is short and jatropha is so vast , Information may be delivered or received operates accurate and Currents. on when STIKe Prima Jambi hearts Still using way users process information delivery , lying between : banners , brochures , advertisements in the print media and others. search google articles for evolving technology as hus band , especially internet , then designed a website Academic Information Systems on STIKes Prima Jambi expected high school hearts can help simplify the delivery process The in information in STIKes Jambi Prima